A new genus and new species of hermit crab (Crustacea: Anomura: Paguroidea: Diogenidae) from the eastern tropical Pacific - Ayón-Parente, Manuel; Hendrickx, Michel E. (Zootaxa, 2010)
Tetralobistes gen. nov., a presently monotypic genus of hermit crab of the family Diogenidae, is described to accommodate a new species, Tetralobistes bicentenarius sp. nov. In many characters, Tetralobistes gen. nov. is similar to Areopaguristes Rahayu & McLaughlin, 2010, Paguristes Dana, 1851, and Pseudopaguristes Mclaughlin, 2002. However, it differs most significantly in the morphology of the male first pleopods and lacks male second and female first pleopods. The most conspicuous character separating Tetralobistes gen. nov. from the other three genera is the shape of the telson, with a typical subdivided (four-lobes) posterior margin.